The Effect of The Animation Video "Known and Protect Yourself" on Knowledge About Sexual Harassment in Children's Elementary School 2 Cinyawang, Patimuan District - Nadeli Triwiono; Suci Ratna Estria (Proceedings Series on Health & Medical Sciences, 2022)
Background: Elementary-aged children are an important period to emphasize about their own safety. This is because at that age children like to spend time with friends. This factor makes children more vulnerable to sexual abuse. Objective: To find out the educational effect of the animated video "know and protect yourself" on the knowledge of prevention of sexual harassment in children at SD N 2 Cinyawang, Patimuan. Method: The research design used was Pre Experimental with the One Group Pretest Posttest Without Control Group Design approach. The sample of this research was 70 students in grades 4 and 5 of SD N 2 Cinyawang. Results: Most respondents were female with a percentage of 50.7%. The average result of sexual harassment prevention knowledge before being given education on the animated video "Know and Protect Yourself" is 5.47, while after being given education it is 8.89. The average difference before and after is 3.42. Conclusion: There is an educational effect of the animated video "Know and Protect Yourself" on knowledge about preventing sexual harassment in children at SD N 2 Cinyawang, Patimuan District (p value 0.000).